A solid base catalyst for catalyzing the synthesis of ethyl methyl carbonate from dimethyl carbonate and ethanol
The preparation of dendritic fibrous silica solid alkali catalyst supported by alkali metal oxides was solved by hydrothermal synthesis, which solved the problems of poor solubility and difficulty in separation of homogeneous catalysts, and achieved efficient reaction between dimethyl carbonate and ethanol to synthesize methyl ethyl carbonate, with high conversion and selectivity, and the catalyst is easy to recover.
Patent Information
- Application Number
- CN202310344964.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-03
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-04-03
AI Technical Summary
In the field of synthesis of ethyl methyl carbonate, homogeneous catalysts have problems such as poor solubility and difficult catalyst separation. The preparation process of heterogeneous catalysts is complicated and has a long reaction equilibrium time, low raw material conversion rate and low selectivity.
A dendritic fibrous silica support was prepared by hydrothermal synthesis using template agents, urea, silicon source and structural guide agents as raw materials, and alkali metal acetate was loaded by impregnation to form a dendritic fibrous silica solid alkali catalyst loaded with alkali metal oxides.
The solid base catalyst has good thermal stability and chemical stability, promotes the transesterification reaction between dimethyl carbonate and ethanol, the conversion rate of dimethyl carbonate is greater than 80%, the selectivity of the product methyl ethyl carbonate is greater than 96%, and the catalyst is easy to recover.
Smart Images

Figure CN116459820B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical synthesis, and particularly relates to a preparation method and application of a solid base catalyst for catalyzing the synthesis of ethyl methyl carbonate from dimethyl carbonate and ethanol. Background Art
[0002] Dimethyl carbonate (DMC) has attracted extensive attention as an intermediate for fine chemicals, biological and pharmaceutical preparations, plasticizers, synthetic lubricants, and organic glass monomers. Ethyl methyl carbonate is an environmentally friendly green chemical that can react with alcohols, phenols, and esters, and is suitable for a variety of organic reaction processes. In addition, ethyl methyl carbonate has low viscosity, high dielectric constant, and good solubility in lithium salts. It can effectively improve the energy density and discharge capacity of lithium-ion batteries, improve battery safety performance, and extend the service life of batteries. It is an excellent organic electrolyte for lithium-ion batteries with high added value and broad development prospects.
[0003] At present, the processes for preparing ethyl methyl carbonate mainly include phosgene method, carbonyl oxidation method and transesterification method. The phosgene method has a high yield, but phosgene is a highly toxic raw material, and the equipment is seriously corroded and polluted, and is a process that is restricted or eliminated. The carbonyl oxidation method uses methanol, ethanol, carbon monoxide and oxygen as raw materials, which are widely available and environmentally friendly, but the production conditions are harsh and the yield is low. The transesterification of dimethyl carbonate has the advantages of low raw material toxicity, low pollution, mild reaction conditions and high yield. Soluble alkali such as NaOH or CH3ONa is a highly active transesterification catalyst, which is also suitable for the transesterification reaction of dimethyl carbonate. Under the conditions of reaction temperature of 40°C, alcohol-ester molar ratio of 3:1 and catalyst molar fraction of 0.15%, the conversion rate of dimethyl carbonate is 82.7%, and the selectivity of ethyl methyl carbonate is 63.2% (Journal of Chemical Engineering, 2014, 28(03): 580-585). Patent CN114210365A reports a process for synthesizing ethyl methyl carbonate from dimethyl carbonate using an alkaline ionic liquid catalyst. When the molar ratio of ethanol to dimethyl carbonate is 4:1, the amount of catalyst accounts for 0.4-0.7% of the total weight of the reactant mixture, and the reaction temperature is 63-64°C, the conversion rate of dimethyl carbonate is 60.45%, and the selectivity of ethyl methyl carbonate is 18.22%. Although the activity of homogeneous catalysts is high, the catalysts are easily deactivated and difficult to separate.
[0004] Heterogeneous solid catalysts such as ion exchange resins, metal oxides and alkaline molecular sieves have the advantages of easy separation from the reaction liquid and high efficiency, and are also used for transesterification reactions. Patent application CN114751827A uses 15% K2CO3 / AC catalyst, the molar ratio of ethanol and dimethyl carbonate is 2:1, the raw materials are gasified and enter the gas phase fixed bed reactor in the form of steam, the reaction temperature is 120-200°C, the reaction pressure is 0.1-0.4MPa, and the liquid hourly space velocity is 11.8h -1 , the conversion rate of dimethyl carbonate is 77.9%, and the selectivity of ethyl methyl carbonate is 51.0%. Patent application CN1900047A loads alkali metal oxides or rare earth metal oxides on porous materials such as alumina and activated carbon. Under the conditions of reaction temperature of 50-110°C, reaction time of 8h, and catalyst dosage of 5-25% of the weight of ethanol, the conversion rate of dimethyl carbonate is 70%. In the reaction of dimethyl carbonate transesterification catalyzed by zeolite and other materials, under the conditions of reaction temperature of 40-75°C, reaction time of 12-26h, catalyst dosage of 2-12% of the mass of dimethyl carbonate, and alcohol-ester molar ratio of 2:1, the conversion rate of dimethyl carbonate is 50%, and the selectivity of ethyl methyl carbonate is 70% (Catalysis Today, 2006, 114, 226-230). Heterogeneous catalysts solve the problem of catalyst separation, but their activity is not as good as homogeneous catalysts, and the preparation process of the catalyst is complicated and the reaction time is long.
[0005] In summary, in the field of synthesis of ethyl methyl carbonate, homogeneous catalysts have problems such as poor solubility and difficulty in catalyst separation, while the preparation process of heterogeneous catalysts is complicated and takes a long time to reach reaction equilibrium, the raw material conversion rate is low, and the selectivity of ethyl methyl carbonate is low. Summary of the invention
[0006] The purpose of the present invention is to provide a solid base catalyst for catalyzing the synthesis of ethyl methyl carbonate from dimethyl carbonate and ethanol in view of the above-mentioned technical problems. The catalyst is easy to recycle and when used for catalyzing the synthesis of ethyl methyl carbonate from dimethyl carbonate and ethanol, the reaction conditions are mild, the process is simple, and the conversion rate of the raw material dimethyl carbonate and the selectivity of the product ethyl methyl carbonate are high.
[0007] The purpose of the present invention is achieved by adopting the following technical solutions:
[0008] A solid base catalyst for catalyzing the synthesis of ethyl methyl carbonate from dimethyl carbonate and ethanol. The solid base catalyst adopts a template agent, urea, a silicon source, and a structure directing agent as raw materials, deionized water and cyclohexane as solvents, and a dendritic fibrous silica carrier is prepared by a hydrothermal synthesis method. Alkali (alkaline earth) metal acetate is used as an alkali (alkaline earth) metal oxide precursor, and the alkali (alkaline earth) metal acetate is loaded on the dendritic fibrous silica carrier by an impregnation method. The dendritic fibrous silica loaded with alkali (alkaline earth) metal oxide is prepared by calcination.
[0009] The solid base catalyst is prepared by a two-step method: dissolving a template and urea (as a hydrolysis agent) in deionized water, stirring at room temperature to completely hydrolyze the template; adding a silicon source, a structure directing agent and cyclohexane, continuing to stir at room temperature to dissolve the silicon source to obtain a white emulsion, placing it at a temperature of 80-100°C for crystallization for 12-24 hours, cooling to room temperature, filtering, washing the filter cake with anhydrous ethanol to remove cyclohexane and water, drying, calcining at a temperature of 400-600°C for 4-8 hours to remove the template, and forming a dendritic fibrous silica carrier; dissolving an alkali (alkaline earth) metal acetate in deionized water, adding the dendritic fibrous silica carrier, stirring and impregnating for 12-24 hours, centrifuging, drying, and calcining at a high temperature of 400-500°C for 2-4 hours to obtain a dendritic fibrous silica loaded with metal oxides.
[0010] The template agent is any one of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride and hexadecylpyridinium bromide.
[0011] The silicon source is any one of tetraethyl silicate, tetramethyl silicate, tetrabutyl silicate, 3-mercaptopropyltrimethoxysilane and phenyltrimethoxysilane, preferably tetraethyl silicate.
[0012] The structure directing agent is any one of n-pentanol, n-butanol, ethylenediamine and triethanolamine, preferably n-pentanol.
[0013] The molar ratio of the template agent to urea is 1:5 to 1:10, preferably 1:6 to 1:9.
[0014] The molar ratio of the template to the silicon source is 1:7 to 1:11, preferably 1:8 to 1:10.
[0015] The molar ratio of the template to the structure directing agent is 1:0.5 to 1:4, preferably 1:1 to 1:3.
[0016] The usage ratio of the structure directing agent to cyclohexane is 0.001:30 to 0.003:30 mol / mL.
[0017] Preferably, the template and urea are dissolved in deionized water, and stirred at room temperature for 3 to 5 hours to completely hydrolyze the template; the silicon source, structure directing agent and cyclohexane are added, and stirring at room temperature is continued for 1 to 2 hours to dissolve the silicon source.
[0018] The present invention has no specific requirements on the usage of deionized water and cyclohexane. Generally, the volume ratio of deionized water to cyclohexane is 1:1.
[0019] The alkali metal acetate is potassium acetate, sodium acetate, lithium acetate, and cesium acetate; the alkaline earth metal acetate is magnesium acetate, calcium acetate, and barium acetate.
[0020] The molar ratio of the alkali metal acetate or alkaline earth metal acetate to the dendritic fibrous silica carrier (relative molecular weight of 60) is 0.1 to 1.2:1, preferably 0.4 to 1.0:1.
[0021] Another object of the present invention is to provide an application of the solid base catalyst in catalyzing the synthesis of ethyl methyl carbonate from dimethyl carbonate and ethanol.
[0022] A method for synthesizing ethyl methyl carbonate comprises: using ethanol and dimethyl carbonate as raw materials, using the solid base catalyst of the present invention as a catalyst, catalyzing dimethyl carbonate and ethanol to synthesize ethyl methyl carbonate; wherein the molar ratio of ethanol to dimethyl carbonate is 1:1-10:1; the solid base catalyst is 1-15% of the mass of dimethyl carbonate; the reaction temperature is 60-150°C; and the reaction time is 2-8h.
[0023] Preferably, the molar ratio of ethanol to dimethyl carbonate is 3:1 to 7:1.
[0024] Preferably, the solid base catalyst is 1 to 9% of the mass of dimethyl carbonate.
[0025] Preferably, the reaction temperature is 70 to 120°C. More preferably, the reaction temperature is 70 to 80°C.
[0026] Preferably, the reaction time is 4 to 8 hours.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The solid base catalyst of the present invention has a dendritic fibrous structure, and adopts metal acetate as a precursor to load metal oxide on a carrier to provide alkaline sites. The solid base catalyst is resistant to high temperature and chemical corrosion (insoluble in solvents such as ethanol), and has good thermal stability and chemical stability, thereby promoting the ester exchange reaction of dimethyl carbonate and ethanol. The synthesis method of the catalyst is simple to operate, mild conditions and the process is environmentally friendly; after the reaction is completed, the catalyst is easy to separate and recover, making the catalytic process more environmentally friendly, which is of great significance to the development and utilization of atom-economic reactions.
[0029] When the dendritic fiber solid base catalyst of the present invention is used to catalyze the synthesis of ethyl methyl carbonate from dimethyl carbonate and ethanol, the reaction conditions are mild and the process is simple. The conversion rate of the raw material dimethyl carbonate is greater than 80%, reaching 91% at the highest, and the selectivity of the product ethyl methyl carbonate is greater than 96%, reaching 99% at the highest. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the SEM image of the catalyst 0.9K2O / SiO2 of Example 1.
[0031] Figure 2 It is the BET diagram of the catalysts prepared in Examples 1 to 5.
[0032] Figure 3 FT-IR spectra of the catalysts prepared in Examples 1 to 5. DETAILED DESCRIPTION
[0033] The present invention is described in more detail below with examples. These examples are merely descriptions of the best mode of carrying out the present invention and do not limit the scope of protection of the present invention in any way.
[0034] Conversion rate of dimethyl carbonate (%) = (molar amount of dimethyl carbonate in reactants - molar amount of dimethyl carbonate in products) / molar amount of dimethyl carbonate in the reaction × 100%.
[0035] Selectivity of ethyl methyl carbonate (%) = molar amount of ethyl methyl carbonate in the product / molar amount of dimethyl carbonate in the reactant × 100%.
[0036] Normal temperature is 25℃.
[0037] Example 1
[0038] 0.36 g of hexadecyltrimethylammonium bromide (template) and 0.54 g of urea (hydrolysis agent) were dissolved in 30 mL of deionized water, and stirred at room temperature for 5 h to completely hydrolyze the hexadecyltrimethylammonium bromide; 1.67 g of tetraethyl silicate (silicon source), 0.088 g of n-pentanol (structure directing agent) and 30 mL of cyclohexane were added, and stirred at room temperature for 1 h to completely dissolve the tetraethyl silicate to obtain a white emulsion; the emulsion was transferred to a hydrothermal synthesis reactor, and crystallized at 100°C for 12 h. The crystallized mixed solution was taken out, cooled to room temperature, filtered, and the filter cake was centrifuged and washed 3 times with anhydrous ethanol, dried, and calcined at 450°C for 7 h to obtain a dendritic fibrous silica carrier (see Figure 1 A).
[0039] Dissolve 0.29 g potassium acetate in 5 mL deionized water, add 0.2 g dendritic fibrous silica carrier, impregnate and stir for 12 h at room temperature; after impregnation, centrifuge, dry, and calcine at 450°C for 3 h to obtain a catalyst, recorded as 0.9K2O / SiO2.
[0040] The SEM image of 0.9K2O / SiO2 is as follows Figure 1 As shown in B, it can be seen that the catalyst 0.9K2O / SiO2 presents a dendritic fiber shape, and the metal loading does not destroy the morphology of the carrier, indicating that the alkali metal can be well loaded on the carrier.
[0041] 4.2mL of dimethyl carbonate and 11.5mL of ethanol (nDMC:nEtOH=1:4) were added to an autoclave reactor equipped with a magnetic stirrer, and 0.225g of 0.9K2O / SiO2 was added at the same time. Nitrogen was introduced to replace the air in the autoclave, and stirring was turned on. After reacting at 80°C for 5h, stirring was stopped, the catalyst was filtered out, and the reaction product was analyzed by gas chromatography. After detection and calculation, the conversion rate of dimethyl carbonate was 91.0%, the selectivity of ethyl methyl carbonate was 98.2%, and the selectivity of diethyl carbonate was 1.8%.
[0042] Example 2
[0043] 0.32 g of hexadecyltrimethylammonium chloride (template) and 0.48 g of urea (hydrolysis agent) were dissolved in 30 mL of deionized water, and stirred at room temperature for 5 h to completely hydrolyze the hexadecyltrimethylammonium chloride; 1.37 g of tetramethyl silicate (silicon source), 0.18 g of n-pentanol (structure directing agent) and 30 mL of cyclohexane were then added, and stirred at room temperature for 1 h to completely dissolve the tetramethyl silicate to obtain a white emulsion; the emulsion was transferred to a hydrothermal synthesis reactor, and crystallized at 80°C for 24 h. The crystallized mixed solution was taken out, cooled to room temperature, filtered, and the filter cake was centrifuged and washed 3 times with anhydrous ethanol, dried, and calcined at 450°C for 7 h to obtain a dendritic fibrous silica carrier.
[0044] Dissolve 0.237 g of magnesium acetate in 5 mL of deionized water, add 0.2 g of dendritic fibrous silica carrier, and impregnate and stir for 12 h at room temperature; after the impregnation, centrifuge, dry, and calcine at 450°C for 3 h to obtain MgO-loaded dendritic fibrous silica, recorded as 0.5MgO / SiO2.
[0045] 4.2mL of dimethyl carbonate and 14.5mL of ethanol (nDMC:nEtOH=1:5) were added to an autoclave reactor equipped with a magnetic stirrer, and 0.405g of 0.5MgO / SiO2 was added at the same time. Nitrogen was introduced to replace the air in the autoclave, and stirring was turned on. After reacting at 120°C for 4 hours, stirring was stopped, the catalyst was filtered out, and the reaction product was analyzed by gas chromatography. After detection and calculation, the conversion rate of dimethyl carbonate was 84.4%, the selectivity of ethyl methyl carbonate was 96.5%, and the selectivity of diethyl carbonate was 3.5%.
[0046] Example 3
[0047] Dissolve 0.38 g of hexadecylpyridinium bromide (template) and 0.48 g of urea (hydrolysis agent) in 30 mL of deionized water, stir at room temperature for 4 hours to completely hydrolyze the hexadecylpyridinium bromide; add 2.56 g of tetrabutyl silicate (silicon source), 0.18 g of ethylenediamine (structure directing agent) and 30 mL of cyclohexane, stir at room temperature for 2 hours to completely dissolve the tetrabutyl silicate to obtain a white emulsion; transfer the emulsion into a hydrothermal synthesis reactor, crystallize at 85°C for 18 hours, take out the crystallized mixture, cool to room temperature, filter, wash the filter cake with anhydrous ethanol by centrifugation for 3 times, dry, and calcine at 550°C for 6 hours to obtain a dendritic fibrous silica carrier.
[0048] 0.252 g of cesium acetate was dissolved in 5 mL of deionized water, and 0.2 g of dendritic fibrous silica carrier was added, and the mixture was impregnated and stirred at room temperature for 24 h. After the impregnation, the mixture was centrifuged, dried, and calcined at 500 °C for 2 h to obtain dendritic fibrous silica loaded with Cs2O, which was recorded as 0.4Cs2O / SiO2.
[0049] 4.2mL of dimethyl carbonate and 20.4mL of ethanol (nDMC:nEtOH=1:7) were added to an autoclave reactor equipped with a magnetic stirrer, 0.045g of 0.4Cs2O / SiO2 was added, nitrogen was introduced to replace the air in the autoclave, stirring was turned on, and after reacting at 90°C for 6h, stirring was stopped, the catalyst was filtered out, and the reaction product was analyzed by gas chromatography. After detection and calculation, the conversion rate of dimethyl carbonate was 82.6%, the selectivity of ethyl methyl carbonate was 97.6%, and the selectivity of diethyl carbonate was 2.4%.
[0050] Example 4
[0051] Dissolve 0.36 g of hexadecyltrimethylammonium bromide (template) and 0.42 g of urea (hydrolysis agent) in 30 mL of deionized water, and stir at room temperature for 3 h to completely hydrolyze the hexadecyltrimethylammonium bromide; add 1.98 g of phenyltrimethoxysilane (silicon source), 0.30 g of triethanolamine (structure directing agent) and 30 mL of cyclohexane, and stir at room temperature for 2 h to completely dissolve the phenyltrimethoxysilane to obtain a white emulsion; transfer the emulsion into a hydrothermal synthesis reactor, crystallize at 90°C for 18 h, take out the crystallized mixed solution, cool to room temperature, filter, wash the filter cake three times with anhydrous ethanol by centrifugation, dry, and calcine at 600°C for 5 h to obtain a dendritic fibrous silica carrier.
[0052] 0.174 g lithium acetate was dissolved in 5 mL deionized water, and 0.2 g dendritic fibrous silica carrier was added, and the mixture was impregnated and stirred at room temperature for 18 h. After the impregnation, the mixture was centrifuged, dried, and calcined at 400 °C for 4 h to obtain dendritic fibrous silica loaded with Li2O, which was recorded as 0.8Li2O / SiO2.
[0053] 4.2mL of dimethyl carbonate and 8.7mL of ethanol (nDMC:nEtOH=1:3) were added to an autoclave reactor equipped with a magnetic stirrer, 0.315g of 0.8Li2O / SiO2 was added, nitrogen was introduced to replace the air in the autoclave, stirring was turned on, and after reacting at 70°C for 8h, stirring was stopped, the catalyst was filtered out, and the reaction product was analyzed by gas chromatography. After detection and calculation, the conversion rate of dimethyl carbonate was 85.9%, the selectivity of ethyl methyl carbonate was 97.8%, and the selectivity of diethyl carbonate was 2.2%.
[0054] Example 5
[0055] Dissolve 0.32 g of hexadecyltrimethylammonium chloride (template) and 0.42 g of urea (hydrolysis agent) in 30 mL of deionized water, and stir at room temperature for 3 h to completely hydrolyze the hexadecyltrimethylammonium chloride; add 2.88 g of tetrabutyl silicate (silicon source), 0.30 g of triethanolamine (structure directing agent) and 30 mL of cyclohexane, and stir at room temperature for 2 h to completely dissolve the tetrabutyl silicate to obtain a white emulsion; transfer the emulsion into a hydrothermal synthesis reactor, crystallize at 90°C for 18 h, take out the crystallized mixed solution, cool to room temperature, filter, wash the filter cake with anhydrous ethanol by centrifugation for 3 times, dry, and calcine at 500°C for 5 h to obtain a dendritic fibrous silica carrier.
[0056] Dissolve 0.162g of sodium acetate in 5mL of deionized water, add 0.2g of dendritic fibrous silica carrier, and impregnate and stir for 18h at room temperature; after the impregnation, centrifuge, dry, and calcine at 400℃ for 4h to obtain Na2O-loaded dendritic fibrous silica, recorded as 0.6Na2O / SiO2.
[0057] 4.2mL of dimethyl carbonate and 17.5mL of ethanol (nDMC:nEtOH=1:6) were added to an autoclave reactor equipped with a magnetic stirrer, and 0.135g of 0.6Na2O / SiO2 was added at the same time. Nitrogen was introduced to replace the air in the autoclave, and stirring was turned on. After reacting at 80°C for 4h, stirring was stopped, the catalyst was filtered out, and the reaction product was analyzed by gas chromatography. After detection and calculation, the conversion rate of dimethyl carbonate was 84.0%, the selectivity of ethyl methyl carbonate was 96.3%, and the selectivity of diethyl carbonate was 3.7%.
[0058] The N2-absorption and desorption of the catalysts prepared in Examples 1 to 5 are shown in the accompanying drawings. Figure 2 As shown, it can be seen that the catalyst has a typical IV type adsorption curve and an H3 type hysteresis loop. Compared with the dendritic fibrous SiO2 carrier of Example 1, the specific surface area of the catalyst of the present invention is reduced, indicating that the metal has entered the pores.
[0059] The infrared spectra obtained in Examples 1 to 5 are as follows: Figure 3 As shown, it can be seen that the catalyst -1 and 1080cm -1 Strong peaks appeared at 3432cm -1 Broad peaks appeared at 475cm, which were attributed to Si-O-Si symmetric stretching mode, asymmetric stretching mode and Si-OH stretching vibration mode. -1 The characteristic absorption peak at 1681cm is caused by the vibration of the M+-O bond structure. -1 The characteristic absorption peak at 2800-3000cm indicates that the water molecules bound to the silica matrix have bending vibration. -1 There are no peaks between the two, indicating that no organic compounds exist in the silica after treatment.
[0060] Example 6
[0061] 0.38 g of hexadecylpyridinium bromide (template) and 0.36 g of urea (hydrolysis agent) were dissolved in 30 mL of deionized water, and stirred at room temperature for 4 h to completely hydrolyze the hexadecylpyridinium bromide; 1.57 g of 3-mercaptopropyltrimethoxysilane (silicon source), 0.22 g of n-butanol (structure directing agent) and 30 mL of cyclohexane were added, and stirred at room temperature for 2 h to completely dissolve the 3-mercaptopropyltrimethoxysilane to obtain a white emulsion; the emulsion was transferred to a hydrothermal synthesis reactor, and crystallized at 100°C for 12 h. The crystallized mixed solution was taken out, cooled to room temperature, filtered, and the filter cake was centrifuged and washed 3 times with anhydrous ethanol, dried, and calcined at 550°C for 6 h to obtain a dendritic fibrous silica carrier.
[0062] Dissolve 0.364g of calcium acetate in 5mL of deionized water, add 0.2g of dendritic fibrous silica carrier, and impregnate and stir for 24h at room temperature; after the impregnation, centrifuge, dry, and calcine at 500℃ for 2h to obtain CaO-loaded dendritic fibrous silica, recorded as 0.7CaO / SiO2.
[0063] 4.2mL of dimethyl carbonate and 20.4mL of ethanol (nDMC:nEtOH=1:7) were added to an autoclave reactor equipped with a magnetic stirrer, and 0.225g of 0.7CaO / SiO2 was added at the same time. Nitrogen was introduced to replace the air in the autoclave, and stirring was turned on. After reacting at 110°C for 7h, stirring was stopped, the catalyst was filtered out, and the reaction product was analyzed by gas chromatography. After detection and calculation, the conversion rate of dimethyl carbonate was 83.3%, the selectivity of ethyl methyl carbonate was 97.2%, and the selectivity of diethyl carbonate was 2.8%.
[0064] Example 7
[0065] 0.36 g of hexadecyltrimethylammonium bromide (template) and 0.54 g of urea (hydrolysis agent) were dissolved in 30 mL of deionized water, and stirred at room temperature for 3 h to completely hydrolyze the hexadecyltrimethylammonium bromide; 2.08 g of tetraethyl silicate (silicon source), 0.06 g of ethylenediamine (structure directing agent) and 30 mL of cyclohexane were added, and stirred at room temperature for 2 h to completely dissolve the tetraethyl silicate to obtain a white emulsion; the emulsion was transferred to a hydrothermal synthesis reactor, and crystallized at 90°C for 18 h. The crystallized mixed solution was taken out, cooled to room temperature, filtered, and the filter cake was centrifuged and washed 3 times with anhydrous ethanol, dried, and calcined at 600°C for 5 h to obtain a dendritic fibrous silica carrier.
[0066] 0.84 g of barium acetate was dissolved in 5 mL of deionized water, and 0.2 g of dendritic fibrous silica carrier was added, and the mixture was impregnated and stirred at room temperature for 18 h. After the impregnation, the mixture was centrifuged, dried, and calcined at 400 °C for 4 h to obtain BaO-loaded dendritic fibrous silica, which was recorded as 1.0BaO / SiO2.
[0067] 4.2mL of dimethyl carbonate and 14.5mL of ethanol (nDMC:nEtOH=1:5) were added to an autoclave reactor equipped with a magnetic stirrer, and 0.315g of 1.0BaO / SiO2 was added at the same time. Nitrogen was introduced to replace the air in the autoclave, and stirring was turned on. After reacting at 100°C for 6h, stirring was stopped, the catalyst was filtered out, and the reaction product was analyzed by gas chromatography. After detection and calculation, the conversion rate of dimethyl carbonate was 85.2%, the selectivity of ethyl methyl carbonate was 98.6%, and the selectivity of diethyl carbonate was 1.4%.
[0068] Comparative Example 1
[0069] 4.2mL of dimethyl carbonate and 11.5mL of ethanol (nDMC: nEtOH = 1:4) were added to an autoclave reactor equipped with a magnetic stirrer, and 0.225g of sodium ethoxide (catalyst) was added at the same time. Nitrogen was introduced to replace the air in the autoclave, and stirring was turned on. After reacting at 80°C for 5h, stirring was stopped, the catalyst was filtered out, and the reaction product was analyzed by gas chromatography. After detection and calculation, the conversion rate of dimethyl carbonate was 89.0%, the selectivity of ethyl methyl carbonate was 46.0%, and the selectivity of diethyl carbonate was 54%.
[0070] Comparative Example 2
[0071] Dissolve 0.51 g of hexadecyltrimethylammonium bromide (template) in 11.7 mL of water, add 3.62 mL of ammonia water (mass concentration of 25%) and mix well, add 2.2 mL of tetraethyl silicate (silicon source) and continue stirring for 2 h, transfer the solution into a hydrothermal synthesis kettle, and hydrothermally heat at 100 ° C for 48 h; take out the crystallized mixed solution, cool to room temperature, centrifuge and wash, dry at 80 ° C for 8 h, and calcine at 550 ° C for 6 h to obtain the carrier MCM-41.
[0072] 0.29 g potassium acetate was dissolved in 5 mL deionized water, 0.2 g carrier MCM-41 was added, and the mixture was immersed and stirred at room temperature for 24 h, centrifuged, dried at 80 °C for 8 h, and calcined at 450 °C for 2 h to obtain a catalyst, which was recorded as K2O / MCM-41.
[0073] 4.2mL of dimethyl carbonate and 11.5mL of ethanol (nDMC:nEtOH=1:4) were added to an autoclave reactor equipped with a magnetic stirrer, and 0.225g of catalyst K2O / MCM-41 was added at the same time. Nitrogen was introduced to replace the air in the autoclave, and stirring was turned on. After reacting at 80°C for 5h, stirring was stopped, the catalyst was filtered out, and the reaction product was analyzed by gas chromatography. After detection and calculation, the conversion rate of dimethyl carbonate was 72.3%, the selectivity of ethyl methyl carbonate was 44.7%, and the selectivity of diethyl carbonate was 55.3%.
[0074] Comparative Example 3
[0075] Dissolve 4 g P123 and 20 mL concentrated hydrochloric acid (mass concentration is 37%) in 105 mL deionized water and stir at a constant temperature of 40°C for 4 h; slowly add 8.6 mL tetraethyl silicate, continue to stir at 40°C for 24 h after the addition is complete, transfer the solution into a hydrothermal synthesis kettle, and hydrothermally heat at 100°C for 48 h; take out the crystallized mixed solution, cool to room temperature, centrifuge and wash, dry at 80°C for 8 h, and calcine at 550°C for 6 h to obtain the carrier SBA-15.
[0076] 0.29 g potassium acetate was dissolved in 5 mL deionized water, 0.2 g SBA-15 was added, and the mixture was immersed and stirred at room temperature for 24 h, centrifuged, dried at 80° C. for 8 h, and calcined at 450° C. for 2 h to obtain the catalyst K2O / SBA-15.
[0077] 4.2mL of dimethyl carbonate and 11.5mL of ethanol (nDMC:nEtOH=1:4) were added to an autoclave reactor equipped with a magnetic stirrer, and 0.225g of catalyst K2O / SBA-15 was added at the same time. Nitrogen was introduced to replace the air in the autoclave, and stirring was turned on. After reacting at 80°C for 5h, stirring was stopped, the catalyst was filtered out, and the reaction product was analyzed by gas chromatography. After detection and calculation, the conversion rate of dimethyl carbonate was 56.4%, the selectivity of ethyl methyl carbonate was 82.3%, and the selectivity of diethyl carbonate was 17.7%.
[0078] Comparative Example 4
[0079] Dissolve 0.6 g urea and 1 g hexadecyltrimethylammonium bromide (template) in 30 mL water, add 4 mL isopropanol and 30 mL cyclohexane; slowly drop 2.7 mL tetraethyl silicate, stir at room temperature for 30 min, transfer the solution to an oven, keep at 80 ° C for 16 h, cool to room temperature, wash by centrifugation, dry at 80 ° C for 8 h, and calcine at 550 ° C for 5 h to obtain a spherical carrier nano-SiO2.
[0080] Dissolve 0.29 g potassium acetate in 5 mL deionized water, add 0.2 g carrier nano-SiO2, soak and stir at room temperature for 24 h, cool to room temperature, centrifuge, dry at 60°C for 8 h, calcine at 450°C for 2 h to obtain catalyst K2O / nano-SiO2.
[0081] 4.2mL of dimethyl carbonate and 11.5mL of ethanol (nDMC:nEtOH=1:4) were added to an autoclave reactor equipped with a magnetic stirrer, and 0.225g of catalyst K2O / nano-SiO2 was added at the same time. Nitrogen was introduced to replace the air in the autoclave, and stirring was turned on. After reacting at 80°C for 5h, stirring was stopped, the catalyst was filtered out, and the reaction product was analyzed by gas chromatography. After detection and calculation, the conversion rate of dimethyl carbonate was 41.5%, the selectivity of ethyl methyl carbonate was 96.4%, and the selectivity of diethyl carbonate was 3.6%.
Claims
1. A method for synthesizing ethyl methyl carbonate, characterized in that: include: Using ethanol and dimethyl carbonate as raw materials and a solid base catalyst as a catalyst, catalyzing dimethyl carbonate and ethanol to synthesize ethyl methyl carbonate; wherein the molar ratio of ethanol to dimethyl carbonate is 1:1-10:1; the solid base catalyst is 1-15% of the mass of dimethyl carbonate; the reaction temperature is 60-150°C; the reaction time is 2-8h; The solid base catalyst is prepared by a hydrothermal synthesis method using a template, urea, a silicon source, and a structure directing agent as raw materials, deionized water and cyclohexane as solvents to obtain a dendritic fibrous silica carrier, and then using an alkali metal acetate or an alkaline earth metal acetate as an alkali metal oxide or an alkaline earth metal oxide precursor, and loading the alkali metal acetate or the alkaline earth metal acetate on the dendritic fibrous silica carrier by an impregnation method, and then calcining to obtain a dendritic fibrous silica loaded with an alkali metal oxide or an alkaline earth metal oxide; The alkali metal acetate is any one of potassium acetate, sodium acetate, lithium acetate, and cesium acetate; the alkaline earth metal acetate is any one of magnesium acetate, calcium acetate, and barium acetate; The molar ratio of the alkali metal acetate or alkaline earth metal acetate to the dendrite fibrous silica carrier is 0.1-1.2:
1.
2. The method for synthesizing ethyl methyl carbonate according to claim 1, wherein: The solid base catalyst is prepared by a two-step method: dissolving a template and urea in deionized water, stirring at room temperature to completely hydrolyze the template; adding a silicon source, a structure directing agent and cyclohexane, stirring at room temperature to dissolve the silicon source, placing at a temperature of 80-100°C for crystallization for 12-24 hours, cooling to room temperature, filtering, washing the filter cake with anhydrous ethanol, drying, and calcining at a temperature of 400-600°C for 4-8 hours to form a dendritic fibrous silica carrier; dissolving an alkali metal acetate or an alkaline earth metal acetate in deionized water, adding the dendritic fibrous silica carrier, stirring and impregnating for 12-24 hours, centrifuging, drying, and calcining at a high temperature of 400-500°C for 2-4 hours to obtain a dendritic fibrous silica loaded with a metal oxide.
3. The method for synthesizing ethyl methyl carbonate according to claim 1 or 2, characterized in that: The template agent is any one of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride and hexadecylpyridinium bromide; The silicon source is any one of tetraethyl silicate, tetramethyl silicate, tetrabutyl silicate, 3-mercaptopropyltrimethoxysilane and phenyltrimethoxysilane.
4. The method for synthesizing ethyl methyl carbonate according to claim 3, wherein: The silicon source is tetraethyl silicate.
5. The method for synthesizing ethyl methyl carbonate according to claim 1 or 2, characterized in that: The structure directing agent is any one of n-pentanol, n-butanol, ethylenediamine and triethanolamine.
6. The method for synthesizing ethyl methyl carbonate according to claim 5, characterized in that: The structure directing agent is n-pentanol.
7. The method for synthesizing ethyl methyl carbonate according to claim 1 or 2, characterized in that: The molar ratio of the template to urea is 1:5-1:10; the molar ratio of the template to the silicon source is 1:7-1:11; and the molar ratio of the template to the structure directing agent is 1:0.5-1:
4.
8. The method for synthesizing ethyl methyl carbonate according to claim 7, wherein: The molar ratio of the template to urea is 1:6-1:9; the molar ratio of the template to the silicon source is 1:8-1:10; and the molar ratio of the template to the structure directing agent is 1:1-1:
3.
9. The method for synthesizing ethyl methyl carbonate according to claim 1 or 2, characterized in that: The usage ratio of the structure directing agent to cyclohexane is 0.001:30 to 0.003:30 mol / mL.
10. The method for synthesizing ethyl methyl carbonate according to claim 1 or 2, characterized in that: The molar ratio of the alkali metal acetate or alkaline earth metal acetate to the dendrite fibrous silica carrier is 0.4-1.0:
1.
11. The method for synthesizing ethyl methyl carbonate according to claim 1, characterized in that: The molar ratio of ethanol to dimethyl carbonate is 3:1-7:1; the solid base catalyst is 1-9% of the mass of dimethyl carbonate; the reaction temperature is 70-120°C; and the reaction time is 4-8h.
12. The method for synthesizing ethyl methyl carbonate according to claim 11, characterized in that: The reaction temperature is 70-80°C.
Citation Information
Patent Citations
Catalyst and method for synthesizing ethyl methyl carbonate and diethyl carbonate
CN114210365A
Method for synthesizing ethyl methyl carbonate and diethyl carbonate
CN114751827A
Process for preparing methyl ethyl carbonate by ester exchanging reaction
CN1900047A
Hierarchical pore nanometer flower-like structure Ag catalyst of methyl glycolate prepared through oxalic ester hydrogenation
CN107442113A
Method for synthesizing ethyl methyl carbonate through porous solid base catalyst
CN109503374A